2020
DOI: 10.7197/cmj.vi.609592
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization of tissues and organs

Abstract: Decellularized tissues and organs have been successfully used in various tissue engineering and regenerative medicine applications. A biological scaffold obtained from the extracellular matrix can be produced by a variety of decellularization methods that effectively remove cells from the tissue to be treated. Decellularization methods is changed according to the target structure of tissues and organs. These methods can be summarized with chemically, physically, enzymatically and using Supercritical Fluid Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Similarly, histological staining indicated almost the same trend in inflammation, dermal cell proliferation, and angiogenesis (Figure 9). Some previous studies reported the same trend, 61,62 while others showed the unintended effects of enzymatic steps on wound healing. The trypsin enzyme cleaves protein subsets through disulfide bonds which eventually causes wound healing postponement and scar tissue formation 63 .…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, histological staining indicated almost the same trend in inflammation, dermal cell proliferation, and angiogenesis (Figure 9). Some previous studies reported the same trend, 61,62 while others showed the unintended effects of enzymatic steps on wound healing. The trypsin enzyme cleaves protein subsets through disulfide bonds which eventually causes wound healing postponement and scar tissue formation 63 .…”
Section: Discussionsupporting
confidence: 52%
“…The elimination of cellular content from natural tissue-derived matrices has the potential to promote healing, integration with host tissues, and limit a foreign body reaction [107]. The decellularization process typically involves the use of chemicals, enzymes, physical forces, and/or a combination of these methods to remove cellular components, while preserving the ECM [108,109]. Methods of decellularization affect the structure of the ECM, the structure of the tissue, and the biomechanical behavior.…”
Section: Decellularizationmentioning
confidence: 99%
“…The elimination of cellular content from natural tissue-derived matrices has the potential to promote healing, integration with host tissues, and limit a foreign body reaction [96]. The decellularization process typically involves the use of chemicals, enzymes, physical forces, and/or a combination of these methods to remove cellular components, while preserving the ECM [97,98]. Methods of decellularization affect the structure of the ECM, the structure of the tissue, and the biomechanical behavior.…”
Section: Decellularizationmentioning
confidence: 99%